2021
DOI: 10.1016/j.ebiom.2020.103150
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional network modulated by the prognostic signature transcription factors and their long noncoding RNA partners in primary prostate cancer

Abstract: Background Transcriptional regulators are seminal players in the onset and progression of prostate cancer. However, clarification of their underlying regulatory circuits and mechanisms demands considerable effort. Methods Integrated analyses were performed on genomic, transcriptomic, and clinicopathological profiles of primary prostate cancer and transcription factor-binding profiles, which included estimating transcription factor activity, identifying transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…As an orally ingested drug, its highest concentration is found in the gastrointestinal (GI) tract, and GI derived tumours would most likely be affected 28 , which further indicates that achieved drug concentration play a major role in tumour responses. This is recapitulated in its various mode of action ranging from influence on microbiota 29 , immune modulation 30 , and direct intracellular effect 31 .…”
Section: Introductionmentioning
confidence: 99%
“…As an orally ingested drug, its highest concentration is found in the gastrointestinal (GI) tract, and GI derived tumours would most likely be affected 28 , which further indicates that achieved drug concentration play a major role in tumour responses. This is recapitulated in its various mode of action ranging from influence on microbiota 29 , immune modulation 30 , and direct intracellular effect 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors are pivotal players in the occurrence and progression of human cancers through various mechanisms, including chromosomal translocations, point mutations, and interaction with lncRNAs [ 27 , 28 ]. Herein, Jaspar software exhibited that there were four binding sites between ETS1 and MKLN1-AS.…”
Section: Discussionmentioning
confidence: 99%
“…As for PCa, a TF named HOXB13 has been found to regulate the lncRNA HOXA11-AS for promoting bone metastasis in PCa, by CCL2/CCR2 cytokine regulation and integrin signaling in autocrine and paracrine processes (76). In recent years, a TF-based regulatory network has been established to clarify the underlying regulation circuits and mechanisms (77)(78)(79)(80). Ning et al (81) constructed a feedforward network mediated by lncRNA and illustrated that many TF-lncRNA interactions were implicated in prognostic motifs.…”
Section: Discussionmentioning
confidence: 99%
“…Ning et al (81) constructed a feedforward network mediated by lncRNA and illustrated that many TF-lncRNA interactions were implicated in prognostic motifs. Jiang et al (77) identified a prognostic signature containing 16 TFs and constructed an interplay network with lncRNAs in PCa. 839 lncRNAs and 124 TFs with 11,398 interactions were found in primary PCa.…”
Section: Discussionmentioning
confidence: 99%